Effect of comprehensive smoke-free legislation on neonatal mortality and infant mortality across 106 middle-income countries - Radó, Márta K. (2022)
Funding Information: We acknowledge the financial support from Dutch Heart Foundation, Lung Foundation Netherlands, Dutch Cancer Society, Dutch Diabetes Research Foundation, Netherlands Thrombosis Foundation, and Health Data Research UK. Publisher Copyright: © 2022 The Author(s). Published by Elsevier Ltd. This is an Open Access article under the CC BY-NC-ND 4.0 license